The Influence of Worklife Balance and Employee Engagement on Employee Performance Intervened by Job Satisfaction Entering the New Normal Era in Education Workplace - Pradita, Novianti Yolan; Sugiarto, Agus (Jurnal Maksipreneur, 2025)
The Covid-19 outbreak is a poignant reminder of how fragile and unpredictable our lives can be in unusual circumstances. Work-life balance and Employee Engagement are two key factors in determining employee performance in the New Normal Era after Covid-19. The intervention of Job Satisfaction can affect assessing the Employee Performance. This research presents each dimension of the variables: Work Life Balance, Work Interference with Personal Life (WIPL), Personal Life Interference with Work (PLIW), Personal Life Enhancement of Work (PLEW), and Work Enhancement of Personal Life (WEPL). The job satisfaction has six dimensions, which are: Salary and Welfare, Work Itself, Leader Behavior, Interpersonal Relationships, Job Competency, and Personal Growth. Employee performance with dimensions which are: Task Performance, Adaptive Performance, and Contextual Performance. Using descriptive analysis, this quantitative research was conducted on 100 employees in Dharma Mulya Christian School. The interesting finding is found during the research whereby in Dharma Mulya Christian School, as an educational workplace, Work Life Balance and Employee Engagement have a significant effect on Job Satisfaction with a positive coefficient direction; nevertheless, Job Satisfaction does not mediate the influence of Work Life Balance and Employee Engagement on Employee Performance.